THE IMPACT OF TRIPLE F-CRISES (FUEL, FOOD, AND FINANCE) ON HOUSEHOLD CONSUMPTION IN INDONESIA - Sriyanto, Sriyanto; Tambunan, Maria R.U.D.; Arifin, Bondi (Universitas Negeri Yogyakarta, 2023)
Post-pandemic challenges are more formidable than during the pandemic. Global supply chain disruptions, geopolitical tensions, the war in Ukraine, and global warming all contribute to the emerging triple crises of fuel, food, and finance. These crises most affect vulnerable households. This study aims to examine the effects of the triple crises on household consumption using consumption theory based on the Keynesian economic model. This research performs a multiple regression model with time-variant and spatial fixed effects and clustering methods on four lower-decile of households across four years, 2019 – 2022, using Susenas data. The findings of the analysis are that the triple crises negatively impact household consumption, with the fuel and food crises showing a significant effect, while the financial crisis does not directly affect consumption. The study proposes a policy recommendation for the government to compensate households for the negative impact of the crisis by providing the amount and the type of policy. In addition, it is best to consider the timing and collaboration opportunity in the implementation phase and set policy success indicators for macro and micro evaluation.